A Miniaturized Periodic Microstrip Leaky Wave Antenna with Shorting Pins - Bin Xi; Yuanxin Li; Yunliang Long (International Journal of Antennas and Propagation)
A miniaturized periodic microstrip leaky wave antenna (MLWA) with shorting pins is proposed in this paper. The suggested antenna consists of a number of stubs that are periodically placed on the side of the transmission line, with the outside edges of the stubs being all integrated with shorting pins. In comparison with the whole-width stubs MLWA, the proposed antenna has an advantage of effective reduction in antenna size for the similar beam-scanning capability. A series of simple and effective equations were obtained to calculate the propagation constant and determine the operating band of the antenna. The consistency of the calculated and measured propagation constant confirms the validity of the parameter equations. As demonstrated by experimental results, the main beam scans electronically and continuously from 145° to 61° in the y-z plane as the operating frequency changes from 5.7 GHz to 11.7 GHz.